Writing class as an activity system: Master’s theses as social texts - He, Fangzhi; Zuo, Yanhong (Journal of International Students, 2026)
Learning to write in a classroom setting also needs to be examined in relation to different elements surrounding the writing class. Following Cultural-historical activity theory (CHAT), this study examined a thesis writing class for international master’s students in a TESOL program in the U.S. Findings indicate that the diverse mediating tools, such as the shared home language and specialized digital software, empowered students to bridge gaps in their existing knowledge. Framing academic integrity as a rule rather than a punitive measure encouraged students to adopt strategies that improved the quality of their work. The system’s division of labor provided emotional support and fostered a sense of community, which was essential for the successful completion of the capstone project. Ultimately, an activity system approach transforms the daunting task of thesis writing from an isolated cognitive struggle into a supported, collective endeavor, making an individually owned capstone work a social text.